Cultural Acculturation of Ring Exchange in the Mappettu Ada Tradition from the Perspective of Islamic Law - Bakri, Kartini (Jurnal Marital: Kajian Hukum Keluarga Islam, 2024)
This research examines the acculturation of ring exchange culture in the mappettu ada tradition carried out by the Cempa community of Pinrang Regency with the problems in the research, namely, First, how is the acculturation of the ring exchange culture in the mappettu tradition in Cempa Pinrang Regency? Second, what is the practice of exchanging rings at the mappettu event in Cempa, Pinrang Regency? Third, what is the review of Islamic law regarding exchanging rings at the mappettu event in Cempa, Pinrang Regency?This research is a type of field research using a normative approach that is descriptive qualitative in nature. The data collection techniques that the author uses are observation and interview techniques.The research results show that: (1) Exchanging rings at the mappettu event is a cultural acculturation process influenced by external factors (Western culture) which is imitated by the Bugis community in Cempa which brings the bride and groom together. (2) In the practice of exchanging rings at the mappettu event in Cempa, Pinrang Regency, namely with the development of modern times, the exchange of rings is carried out like a party by decorating the room, the bride and groom put rings on each other. gold ring directly on the left ring finger. (3) Judging from Islamic law, the practice of exchanging rings is not in accordance with the Shari'a where in practice there are elements between the prospective groom and the prospective bride touching each other when pairing the rings. The use of gold on men is also prohibited in Islamic law, although only a little, and is permitted for women as explained in the hadith. Keywords: Acculturation,Exchange Rings, Islamic Law